Framework for Analysing Educational Equity in the English Education System - Agri, Dalida; Berry, Anthony; Arandia, Juliette; Anastasia, Ellena (SCAD Independent, 2018)
Equity has become a pressing issue in debates about education reform in England, as new policy approaches have been sought to break the link between social advantage and educational achievement. Conflicting notions of what an equitable education system would look like and how it can be achieved, have led to discord at the heart of government, yet what is meant by equity is often unclear, and there are underlying tensions within the government’s dual excellence-and-equity agenda. The argument put forward here is that for reforms to have wide-reaching and equitable impacts, they must be based on broader notions of equity and education than those currently prevalent at policy level. To this end, a framework for thinking about educational equity is developed, exploring notions of equity per se, and the range of educational arenas in which equity might be pursued. This framework is intended to guide the creation of a systematic evidence-base about equity in education which can, in turn, inform policy.